A microbial survey of food served to Oncohematology patients at a University Hospital - Khamis, Nagwa Abdel-Ghani; Hafez, Hala Mahmoud (International Journal of Infection Control, 2010)
Although everyone is susceptible to foodborne diseases, the immunocompromised patients are particularly at risk of contracting foodborne illnesses and suffer more serious sequelae as a result of infection. The aim of the present work was to measure the degree of microbial contamination in different food stuffs, served to immunocompromised patients admitted at the Oncohematology unit in our hospital. Several types of foods were selected from those served to the oncohematology patients in our hospital. Samples of each food were taken at random from the central kitchen, the wards’ pantry as well as from the patients. Food included processed food stuffs as well as non-processed food stuffs. Samples were processed according to the protocol obtained from the Centre Hospitalier Universitaire Bicêtre (2001). The total bacterial count, the total coliform count, the presence of Staphylococcus aureus, as well as the presence of fungal food contamination were determined and values obtained were compared to the accepted values cited in the protocol provided by the CHU Bicêtre (2001). Twenty one out of 28 examined processed food samples (75%) were free from any contamination. The remaining 7 samples (25%) yielded positive results on culture, yet the counts were considered acceptable. On the other hand, all of the non-processed food samples examined were contaminated (100%). Identified organisms were Pseudomonas, Aeromonas, Enterocci, Diphtheroid and Anthracoid. All examined samples were positive for fungal contamination with Aspergillus niger being the most commonly isolated mold. We concluded that non-processed food represents a potential risk of microbial exposure to the immunocompromised patients.